2021
DOI: 10.1128/spectrum.00805-21
|View full text |Cite
|
Sign up to set email alerts
|

Similar Methanogenic Shift but Divergent Syntrophic Partners in Anaerobic Digesters Exposed to Direct versus Successive Ammonium Additions

Abstract: Anaerobic digestion (AD) is an attractive biotechnological process for wastewater bioremediation and bioenergy production in the form of methane-rich biogas. However, AD can be inhibited by ammonium generated by protein-rich effluent, commonly found in agro-industrial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Meanwhile, the relative abundance of Sporanaerobacter sp. (carbohydrate hydrolysis-related bacteria), which could accelerate carbohydrate hydrolysis and convert carbohydrates to butyric acid, 50 was improved from 0.36 to 9.61% after enzymatic pretreatment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the relative abundance of Sporanaerobacter sp. (carbohydrate hydrolysis-related bacteria), which could accelerate carbohydrate hydrolysis and convert carbohydrates to butyric acid, 50 was improved from 0.36 to 9.61% after enzymatic pretreatment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the relative abundance of Sporanaerobacter sp. (carbohydrate hydrolysis-related bacteria), which could accelerate carbohydrate hydrolysis and convert carbohydrates to butyric acid, was improved from 0.36 to 9.61% after enzymatic pretreatment. Since the pH values of all reactors were controlled at 6 and the content of soluble reducing sugar (the representative carbohydrate) in the mixed enzymatic pretreatment reactor (41352 mg/L) was significantly higher than that in the unpretreated reactor (14536 mg/L), these conditions might be beneficial for the enrichment of these VFA formation-related bacteria, resulting in remarkable VFA promotion.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). It has been reported that low formate concentrations (2 mM) can have notorious effects on microbial growth and activity [ 58 , 60 ]; but also microbial acclimation after short-term sequential batch incubation [ 61 ] could have played a role in the observed differences between phase II-A and II-C in the treatments of experiment II. More experimental work including incubations in parallel is required to differentiate effects associated with formate addition and microbial acclimation.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential batch experiments were carried out to investigate the effect of successive changes in operational conditions (e.g., high S/X ratio and addition of formate as external electron donor) on carboxylates and CH 4 production under elevated pCO 2 (5 bar). Batch incubation modality was selected based on the premise of anticipated differentiated microbial community responses depending on the way the stress condition is applied (direct vs. successive), as reported for other stressors such as high NH 4 + concentrations [ 61 ]. An operational pressure of 5 bar pCO 2 was selected as a boundary condition between extended lag-phases and noticeable CO 2 effects on substrate conversion based on previous work [ 29 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, hydrolytic and acidogenic bacteria break down complex organic molecules into volatile fatty acids (VFAs, e.g., butyric acid, propionic acid, acetic acids, etc. ), dihydrogen (H 2 ), and carbon dioxide (CO 2 ) via hydrolysis, acidogenesis, and acetogenesis ( Hardy et al, 2021 ). Then, acetoclastic (e.g., Methanosaetaceae , Methanosarcinaceae ) and hydrogenotrophic (e.g., Methoanomicrobiales , Methanobacteriales ) methanogenic archaea produce CH 4 from acetate and H 2 /CO 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%